ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN SELF EFFICACY SISWA SMP TERHADAP SOAL PERSAMAAN GARIS LURUS - Gita Sri Indani Rahayu; Luvy Sylviana Zanthy (Journal on Education, 2019)
The purpose of this descriptive study was to determine the ability of creative thinking and self-efficacy mathematical students of class VIII SMP Pasundan 1. The subject of this research is students of class VIII which consists of 36 students. Data collection techniques namely the test sheet mathematical creative thinking abilities of students and the questionnaire of self efficacy (Mastery Experience, Vicarious Experience, Verbal Persuasion, and Physiological and Affective states), interview and documentation. Based on the analysis of data ability to think creatively and questionnaires self efficacy, showed that the creative thinking Abilities of JUNIOR high school students Pasundan 1 Cimahi class VIII on the material equation of a straight line is already largely achieve the indicator of the ability to think creatively. This is indicated by the percentage of the ability of mathematical creative thinking reached 69%, Self-efficacy mathematical students of SMP Pasundan 1 Cimahi class VIII in the material equation of a straight line in the category that most is good. It is based on the results of the percentage of self efficacy up to 61%, and Self-efficacy mathematical students who have confidence will be successful in resolving the matter affects the level of mathematical creative thinking of students.